A simple strategy that may effectively tackle the anode-electrolyte interface issues in solid-state lithium metal batteries - Liu, Bo; Du, Mingjie; Chen, Bingbing; Zhong, Yijun; Zhou, Jianqiu; Ye, Fei; Liao, Kaiming; Zhou, Wei; Cao, Chencheng; Cai, Rui; Shao, Zongping (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Contact issue of the anode-electrolyte interface was tackled by a Li-Mo composite.•Lower cohesive energy and higher binding energy are beneficial to better contact.•Symmetric cell shows a high critical current density and a stable 1200-h cycling.•A full cell with a LiFePO4 cathode presented stable performance for 200 cycles.•The work provides a facile and feasible way to overcome interface problems. Interface issues are the biggest challenges that hindering the commercialization of solid-state lithium metal batteries (SSLMBs). Here, we propose a novel strategy targeting for effectively resolving the tedious lithium-garnet solid electrolyte interface problem from the lithium side. We intentionally introduce α-MoO3 nanobelts into the molten metallic lithium, forming a Li-Mo composite. Compared to molten lithium, the composite improves wettability on the garnet electrolyte. As revealed by density functional theory calculations, such improvement could be ascribed to the reduced cohesive energy and the improved interface binding energy to the LLZTO. Intimate surface contact can be easily achieved without complicated surface treatment, which not only significantly reduces the interface resistance to ~ 1 Ω cm2, but could also effectively inhibits the generation of lithium dendrites. These features ensure a significant critical current density of 1700 µA cm−2 and a stable electrochemical Li plating/stripping process for more than 1200 h. A full cell with the Li-Mo composite anode and LiFePO4 cathode also presents a fairly stable cycling performance at room temperature. Different from most previous strategies that try to tackle the interface issues from the electrolyte side, our research results suggest that designing lithium composite anodes with low cohesive energy and high interface binding energy to the solid electrolyte is an attractive and feasible solution to overcome interface problems.